Early Detection of Severe Acute Respiratory Syndrome Coronavirus 2 Antibodies as a Serologic Marker of Infection in Patients With Coronavirus Disease 2019. (1st May 2020) - Rongqing, Zhao; Li, Maohua; Song, Hao; Chen, Jianxin; Ren, Wenlin; Feng, Yingmei; Gao, George F; Song, Jinwen; Peng, Ya; Su, Bin; Guo, Xianghua; Wang, Yanjun; et al.
Abstract: Background: Thousands of medical staff have been infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with hundreds of deaths reported. Such loss could be prevented if there were a serologic assay for SARS-CoV-2–specific antibodies for serological surveillance of its infection at the early stage of disease. Methods: Using Chinese hamster ovarian (CHO) cell–expressed full-length SARS-CoV-2 S1 protein as capturing antigen, a coronavirus disease 2019 (COVID-19)/SARS-CoV-2 S1 serology enzyme-linked immunosorbent assay (ELISA) kit was developed and validated with negative samples collected prior to the outbreak or during the outbreak and positive samples from patients confirmed with COVID-19. Results: The specificity of the ELISA kit was 97.5%, as examined against total 412 normal human samples. The sensitivity was 97.1% by testing against 69 samples from hospitalized and/or recovered COVID-19 patients. The overall accuracy rate reached 97.3%. The assay was able to detect SARS-CoV-2 antibody on day 1 after the onset of COVID-19 disease. The average antibody levels increased during hospitalization and 14 days after discharge. SARS-CoV-2 antibodies were detected in 28 of 276 asymptomatic medical staff and 1 of 5 nucleic acid test–negative "close contacts" of COVID-19 patients. Conclusions: With the assays developed here, we can screen medical staff, incoming patients, passengers, and people who are in close contact with the confirmed patients to identify the "innocent viral spreaders, " protect the medical staff, and stop further spread of the virus. Abstract : A highly specific and very sensitive serological severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody assay with overall accuracy at 97.3% was developed using CHO-expressed SARS-CoV-2 S1 protein for screening of medical staff and others for SARS-CoV-2 infection.